1997
DOI: 10.1002/(sici)1098-2744(199710)20:2<162::aid-mc2>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Association of a murine chromosome 9 locus (Psl1) with susceptibility to mouse skin tumor promotion by 12-O-tetradecanoylphorbol-13-acetate

Abstract: It has been known for many years that there are dramatic differences in the susceptibility of mouse stocks and strains to two-stage skin carcinogenesis and that these differences are due the animals' responsiveness to tumor-promoting agents. In earlier studies using several inbred mouse strains, we found that susceptibility to skin tumor promotion by phorbol esters such as 12-O-tetradecanoylphorbol-13-acetate (TPA) is a multigenic trait. To extend this work, we conducted a genome scan of (C57BL/6 x DBA/2)F1 x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 18 publications
(19 reference statements)
6
37
0
Order By: Relevance
“…These studies identified a ''promotion-susceptibility'' locus on chromosome 9 (D9Mit271; 48 cM; ref. 19) close to the Skts6 locus (D9Mit76; 49 cM) and a locus designated Skts4 on chromosome 5 (20). Although direct comparisons are complicated by differences in the methodologies used, these results involving intraspecific crosses contrast with the relatively large number of strong modifier loci detected in the Mus spretus͞Mus musculus backcross described in this report.…”
Section: Discussionmentioning
confidence: 55%
“…These studies identified a ''promotion-susceptibility'' locus on chromosome 9 (D9Mit271; 48 cM; ref. 19) close to the Skts6 locus (D9Mit76; 49 cM) and a locus designated Skts4 on chromosome 5 (20). Although direct comparisons are complicated by differences in the methodologies used, these results involving intraspecific crosses contrast with the relatively large number of strong modifier loci detected in the Mus spretus͞Mus musculus backcross described in this report.…”
Section: Discussionmentioning
confidence: 55%
“…d The combined LOD equivalent score, is the sum of the individual LOD equivalent scores, was calculating using the program Qlink. overlap between a locus involved in skin tumor promotion, Psl1, previously mapped to a region of Chromosome 9 (Angel et al, 1997), and the Ksc1 locus (Popova et al, 2003). Moreover, Mock et al (1998) reported a higher than expected linkage score for the marker D9Mit271 (48 cM) in association with skin tumor susceptibility.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, two genetic linkage studies performed in genetic crosses in which both parental strains carried the same Tyr allele, either functional (Angel et al, 1997) or albino (Mock et al, 1998), did not detect any skin tumor-modifier locus in the Tyr region; a test locus cannot exert allele-specific phenotypic effects in a cross originating from two strains carrying the same allele (Manenti et al, 1997).…”
Section: Discussionmentioning
confidence: 96%